Analisis Perhitungan Poros Roda Depan Motor Yamaha Vixion Advance 150CC 2015 - Luthfi Rachman Sidqi; Kardiman Kardiman; Najmudin Fauji (Jurnal Ilmiah Wahana Pendidikan, 2022)
The front Shaft of a motorcycle works to support the steering load to maintain the balance of the vehicle when walking, looking for the road and reducing speed. In this study, the engine elements will be planned based on systematic calculations and at the same time implementing, applying theory in the form of engine element structures, especially on the front shaft of the 2015 Yamaha Vixion Advance 150cc motorcycle. The data analyzed is the static calculation on the motorcycle and on the bicycle shaft. 2015 Yamaha Vixion Advance 150cc motorcycle. With the calculation of 2015 Yamaha Vixion Advance 150cc motorcycle statics, the number = V1:1231 N, V2: -59 N, V3, -859 N, M1: 860 N.mm & 837,080 N.mm, M2: 378,420 N.mm&318240 N.mm, M3: 135,760 N.mm&1.187,280 N.mm. and the results of statics on the shaft of the 2015 Yamaha Vixion Advance 150cc motorcycle the number = V1: 615.5 N, V2: 615.5 N, V3: 0 N, M1: -2160 N.mm&-39053,75 N.mm, M2 : 122484.5 N.mm&244969 N.mm, M3: 12310 N.mm&12310 N.mm